Features of Balance Model Development of Exclave Region - Gareev, Timur Rustamovich; Voloshenko, Kseniya Yuryevna (Economy of Regions, 2015)
In the article, the authors build a balance model for an exclave region. The aim of the work is to explore the unique properties of exclaves to evaluate the possibility of development of a more complex model for the economy of a region. Exclaves are strange phenomena in both theoretical and practical regional economy. There is lack of comparative models, so it is typically quite challenging to study exclaves. At the same time, exclaves produce better statistics, which gives more careful consideration of cross-regional economic flows. The authors discuss methodologies of model-based regional development forecasting. They analyze balance approach on a more general level of regional governance and individually, on the example of specific territories. Thus, they identify and explain the need to develop balance approach models fitted to the special needs of certain territories. By combining regional modeling for an exclave with traditional balance and simulation-based methods and event-based approach, they come up with a more detailed model for the economy of a region. Having taken one Russian exclave as an example, the authors have developed a simulation event-based long-term sustainability model. In the article, they provide the general characteristics of the model, describe its components, and simulation algorithm. The approach introduced in this article combines the traditional balance models and the peculiarities of an exclave region to develop a holistic regional economy model (with the Kaliningrad region serving as an example). It is important to underline that the resulting model helps to evaluate the degree of influence of preferential economic regimes (such as Free Customs Zone, for example) on the economy of a region.